INTEGRATING ULTRAMAFIC LAMPROPHYRES INTO THE IUGS CLASSIFICATION OF IGNEOUS ROCKS: RATIONALE AND IMPLICATIONS - Tappe S.; Foley S.F.; Jenner G.A.; Kjarsgaard B.A. (My University, 2005)
We introduce a modification to the current IUGS classification system for igneous rocks to include ultramafic lamprophyres, which are currently entirely omitted. This is done by including a new step in the sequential system, after the assignment of pyroclastic rocks and carbonatites, that considers ultramafic inequigranular textured rocks with olivine and phlogopite macrocrysts and/or phenocrysts. At this step ultramafic lamprophyres are considered together with kimberlites, orangeites (former Group 2 kimberlites) and olivine lamproites. This proposal allows the correct identification and classification of ultramafic lamprophyres within the IUGS scheme. Only three end-members are required for describing the petrographic and compositional continuum of ultramafic lamprophyres: alnoite (essential groundmass melilite), aillikite (essential primary carbonate) and damtjernite (essential groundmass nepheline and/or alkali feldspar). It is argued that all ultramafic lamprophyre rock types can be related to a common magma type which differs in important petrogenetic aspects from kimberlites, orangeites, olivine lamproites and the remainder of lamprophyres such as alkaline and calc-alkaline varieties. Ultramafic lamprophyres can be readily distinguished from olivine lamproites by the occurrence of primary carbonates, and from kimberlites by the presence of groundmass clinopyroxene. In other cases distinction between aillikites, kimberlites and orangeites must rely on mineral compositions in order to recognize their petrogenetic affinities.